Contribution Factors on Early Initiation of Breastfeeding - Dwi Fitria Ariyani; Lina Handayani (International Journal of Public Health Science (IJPHS), 2015)
One of the causes of high Infant Mortality Rate is the low coverage of exclusive breastfeeding. One of the supporting factors to exclusive breastfeeding is implementation of Early Initiation of Breastfeeding (EIB). Mother’s knowledge and understanding about the EIB, as well as the role of birth attendants, especially midwives can be strongly support it’s the EIB. The purpose of this research was to determine the relationship between mother's knowledge, mother’s attitudes and midwife role with the implementation of Early Initiation of Breastfeeding (EIB). The research was an observational analytic research employed cross sectional design. The subjects were maternity mothers who inpatient at Pulang Pisau Hospital in Central Kalimantan Province, Indonesia. The results showed that there were significant relationships between mother's knowledge, attitudes and midwife role with the Implementation of Early Initiation of Breastfeeding (EIB). Attitude was the most influenced variable to the EIB.